Where There Are No Therapists: The Related Services Assistant Alternative - Nancy B. Robinson; Wendy L. Tada; Mellanie Lee; Alan Atkinson; Natalia Rekemesik (Journal of Research in Rural Education, 1998)
Chronic shortages ofrelated services personnel in the areas ofphysical therapy, occupational therapy, and speechlanguage pathology have severely limited servicesforstudents with disabilities in rural areas ofthe U.S. Pacific jurisdictions. A training model with a functional approach to support students with severe disabilities to achieve IEP objectives was developed and implemented in partnership between the College of Micronesia, Federated States of Micronesia (FSM), and the Hawaii University Affiliated Program at the University of Hawaii. Nineteen teachers completed the training program, with positive impacts for students reported by families, teachers, and administrators in the FSM. Discussion focuses on the challenges and implications, of the Related Services Assistant training model to implement functional supports where related services are lacking in rural communities.